The effectivity of 2% salicylic acid on inflammatory acne vulgaris. - Theresia Niken Wijayanti, Theresia Niken Wijayanti (Universitas Gadjah Mada, 2001)
Background: The patients compliance is very important for the successful of acne management. Two percent of salicylic acid lotion can be used for treatment of non comedogenic acne, and as moisturizer. Objective: This study was aimed to evaluate the effect of 2% salicylic acid on inflammatory acne vulgaris patients.Material and Method: A randomized clinical trial was done in two groups of inflammatory acne vulgaris patients or grade I, II, and III papulopustular acne vulgaris according to Plewig Kligmans classification. The first group was treated with doxycycline 50 mg once daily and 2% salicylic lotion, and the other group as a control was treated with doxycycline 50 mg once daily plus vehicle lotion. Evaluation was done by counting the non-inflammatory and inflammatory lesions, measuring skin lightness of the skin using chromameter, and the subjects opinion of their skin conditions about smoothness and moistness of the skin using visual analog scale. In the beginning of this study, there were 78 subjects participated. However, only 62 subject completed this study with 12 weeks. The differences of non-inflammatory lesions, inflammatory lesions, and the subjects opinion of their skin conditions were analyzed using Mann-Whitney Test. The difference of lightness of the skin was analyzed using independent sample t-test. Result: The result of this study showed that there were significant differences (p value< 0.05) in the reduction of non-inflammatory lesions, inflammatory lesions, and the increasing of lightness of the skin between both groups. No significant differences were found (p value>0.05) in the smoothness, and moistness of the skin.Conclusion: The effectivity of 2% salicylic acid on the inflammatory acne patients were the reduction of non-inflammatory and inflammatory lesions, and the increasing of lightness of the skin.Keywords: salicylic acid, acne lesions, smoothness, moistness, lightness